(untitled) (Fractal: Journal of Psychology, 2009)
Departing from a well established problem in the field of psychology - the interaction between the individual and space - we intend to step back and question the understanding of this very articulation. Traditionally understood as the mutual influence of clearly delimited objects, we intend to point, proposing an analysis of the articulations between subjectivities and urban spaces in modernity, that none of them exists as given data. We shall point, therefore, that the rationalization of space and the individualization of the existence are woven in a web of fragmented relations that mark modern experience, which dissolves, taints, their a-historicity, their inexorability.